Daughters of polycystic ovary syndrome pregnancies and androgen levels in puberty: a Meta-analysis. (3rd October 2022) - Valsamakis, Georgios; Violetis, Odyssefs; Chatzakis, Christos; Triantafyllidou, Olga; Eleftheriades, Makarios; Lambrinoudaki, Irene; Mastorakos, George; Vlahos, Nikos F.
Abstract: Purpose : To provide an overview and critical analysis of the literature related to the circulating androgen levels of daughters of PCOS mothers during prepubertal and pubertal stage who have not yet been diagnosed with PCOS or precocious puberty. Methods : We critically considered and meta-analyzed observational studies comparing androgens concentration in daughters of PCOS mothers compared to daughters of mothers without PCOS. A literature search was conducted in MEDLINE, Scopus and other sources from 01/09/2021 until 01/12/2021. The study followed the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA). The primary outcome included total testosterone levels whereas the secondary outcomes included 17a-hydroxyprogesterone (17-OHP), androstenedione (Δ4Α) and Sex Hormone Binding Globulin (SHBG) levels respectively. Results : Our search yielded 1073 studies, 9 of which were included in our analysis. The results are presented differently according to pubertal stage. Pubertal daughters of PCOS mothers exhibited significantly higher total testosterone (pooled mean difference 14.95 (95%CI: 6.98 to 22.93), higher 17-OHP (pooled mean difference 0.11 (95%CI: 0.02 to 0.20) and lower SHBG levels (pooled mean difference −10.48 (95%CI: −16.46 to −4.61). Instead, prepubertal daughters of PCOS mothers presented greater SHBG levels (pooled mean difference 7.79 (95%CI: 0.03 to 15.54) compared to controls. No difference was found in Δ4Α levels in both groups. Conclusion : The onset of puberty is a critical point in the development of the disease and an early intervention may be imperative.